E-Business in Ukraine: Peculiarities, Tendencies, Prospects - Lipych, Liubov H.; Mokhniuk, Anna M. (Lesya Ukrainka Eastern Europen National University, 2020)
Introduction. It is evident that the electronic business plays a central role in the economy development, facilitating the exchange of information, goods, services, and payments. We feel very strongly that entrepreneurs who understand the role and significance of e-business and are ready to meet the sharply expanding scale of cross-border e-commerce will be the winners of tomorrow in the world market. An initial point to underline in connection with these tendencies is that business which does not give some attention to e-business and e-marketing promotion could very easily loose its place on the market. This explains the hyper attention to the e-business nowadays and as a result the necessity of studying this question. The purpose of the article is to study the characteristic features of e-business in Ukraine, to determine the latest tendencies of its development and to propose the certain steps to increase its growth. Results. Recent researches support the view that organizations can have a significant benefit of using e-business tools in their everyday operations. The article examines the benefits, problems and limitations of e-business in Ukraine. It has been distinguished that Ukraine is an attractive market for the development of e-commerce. It has a large potential for e-business and its related activities. In 2018 Ukraine ranked the 2nd place in the turnover growth of online usage among European countries. A major factor stimulating Internet growth is the drastic improvement of the telecommunications infrastructure in the country. Advantages and risks of new electronic marketing techniques were considered in the article. The main strengths of online marketing system are high quality customer service, greater reach, time saving customer loyalty, easy access to information, 24 hours access and personal contact with the customer. Considering the risks, it was admitted that e-marketing requires considerable time investment to get the results and it takes a long time to generate meaningful interactions. Conditions that should be arranged for successful e-business model implementation were determined. It was pointed out that in order to increase the development of e-business in Ukraine that certain steps such as harmonizing of essential laws and standards to the European ones, enhancing the use of web analytics tools, providing an appropriate choice of communication channels and improving administrative regulations regarding e-business procedures should be taken. In this regard, Ukrainian businesses need all the support they can get from policymakers and regulators in order to be able to grow in an increasingly competitive global market. In conclusion, in order to stay effective, to improve operational efficiency, profitability, and to strengthen their competitive position business organizations should definitely adopt e-business model. It is not enough to have high quality products or services to operate successfully in the market; productive introduction of new e-business models is vital in a computerised electronic environment. In this regard, if Ukrainian government wants its companies to fully play their role in a globalized world, it needs to create a harmonized market and a favourable environment where domestic e-business companies can flourish. Prospects for further research can be seen in the analysis of the methods of measuring the effectiveness of different e-business models.
Keywords: e-business; e-commerce; e-marketing; business model; new technologies; exchange of information